Artificial Intelligence: Transformasi Pendidikan Islam di Era Digital - Yusba Alhamda Syari (Raudhatun Najah Publisher, 2025)
The rapid advancement of Artificial Intelligence (AI) has transformed educational practices, including Islamic education for children. Despite its potential to enhance learning effectiveness, studies integrating pedagogical, ethical, and spiritual dimensions within Islamic education remain limited. This study examines the transformation of Islamic education in the AI era, focusing on changes in learning paradigms, opportunities for AI integration, ethical-spiritual challenges, and the reconstruction of teachers’ roles. Using a qualitative library research approach, the study employs a critical-conceptual analysis of scholarly literature on AI, digital pedagogy, and Islamic education. The findings indicate that AI can strengthen Islamic education through technology-assisted Qur’anic learning, personalized instruction, interactive learning media, data-driven assessment, and the promotion of Islamic digital literacy. However, its integration also raises concerns regarding the dehumanization of learning, technology dependency, weakened scholarly authority, algorithmic bias, and reduced spiritual engagement. This study proposes three conceptual frameworks—Islamic AI-Based Education Framework, Islamic Ethical AI Framework, and Islamic AI-Educator Framework—to align technological innovation with Islamic values. The study concludes that effective AI integration requires balancing digital transformation with the development of knowledgeable, ethical, and spiritually conscious Muslim generations.